More Observations on "Renegade View of What We Do" - Robert E. Enlow (Journal of Applied Communications, 1979)
Planning Evaluation Overcome Bored Writing, Editing "We do have a problem..." "No one is immune..." I was pleased to hear Don Wells use these words, because we are all part of the same profession. And, where one stumbles, all suffer.